Survey of the incidence of tetracycline-resistant haemolytic streptococci between 1958 and 1965 - Dadswell, J. V. (1967)
The incidence of tetracycline-resistant beta-haemolytic streptococci isolated in the Department of Pathology and Bacteriology of the Institute of Laryngology and Otology, London, during the years 1958-65 is reported. From less than 1% of all beta-haemolytic streptococci isolated in 1958 they increased to 44% in 1965. These findings are discussed.